CORPORATE GOVERNANCE COMMITTEE AND FINANCIAL PERFORMANCE OF TELECOMMUNICATION FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study examined the effect of the corporate governance committee and the financial performance of telecommunication firms in Nigeria. The specific objectives are to: find out the significant effect between audit committee size and the net profit margin of listed telecommunication firms in Nigeria, and examine the effect between the remuneration committee and the net profit margin of listed telecommunication firms in Nigeria and Ex-Post Fact research design was employed for this study. Data were extracted from annual reports and accounts of the telecommunication firms listed in Nigeria Exchange Group from, 2013 to 2022. The data were analysed comparatively via both descriptive and inferential analyse. The descriptive statistics was first conducted in order to gain understanding of the sample characteristics as regards the selected variables. Inferential statistical analysis was carried out using Panel Least Square (PLS) regression analysis via E-Views 9.0 statistical software. The study revealed that audit committee size and remuneration committee have a positive significant effect on net profit margin of telecommunication firms in Nigeria. The study thereby recommended among others that firm should sustain audit committee, so as to ensure that the committee has enough time to take decisions that are efficient and effective in enhancing better firm performance, as well make sure that the businesses are adherence to policies, rules, procedures code of conduct and regulations.
Keywords: Audit committee size; Corporate governance; Net profit margin; Remuneration committee